Mechanosensitivity of Human Oligodendrocytes - Espinosa-Hoyos, Daniela; Burstein, Suzanne R.; Cha, Jaaram; Jain, Tanya; Nijsure, Madhura; Jagielska, Anna; Fossati, Valentina; Van Vliet, Krystyn J. (Frontiers in Cellular Neuroscience, 2020)
Oligodendrocytes produce and repair myelin, which is critical for the integrity and function of the central nervous system. Oligodendrocyte and oligodendrocyte progenitor cell biology is modulated in vitro by mechanical cues within the magnitudes observed in vivo. In some cases, these cues are sufficient to accelerate or inhibit terminal differentiation of murine oligodendrocyte progenitors. However, our understanding of oligodendrocyte lineage mechanobiology has been restricted primarily to animal models to date, due to the inaccessibility and challenges of human oligodendrocyte cell culture. Here we probe the mechanosensitivity of human oligodendrocyte lineage cells derived from human induced pluripotent stem cells. We target phenotypically distinct stages of the human oligodendrocyte lineage and quantify the effect of substratum stiffness on cell migration and differentiation, within the range documented in vivo. We find that human oligodendrocyte lineage cells exhibit mechanosensitive migration and differentiation. Further, we identify two patterns of human donor line-dependent mechanosensitive differentiation. Our findings illustrate the variation among human oligodendrocyte responses, otherwise not captured by animal models, that are important for translational research. Moreover, these findings highlight the importance of studying glia under conditions that better approximate in vivo mechanical cues. Despite significant progress in human oligodendrocyte derivation methodology, the extended duration, low yield, and low selectivity of human induced pluripotent stem cell-derived oligodendrocyte protocols significantly limit the scale-up and implementation of these cells and protocols for in vivo and in vitro applications. We propose that mechanical modulation, in combination with traditional soluble and insoluble factors, provides a key avenue to address these challenges in cell production and in vitro analysis.